2020
DOI: 10.1111/ajco.13368
|View full text |Cite
|
Sign up to set email alerts
|

Value of 3Tesla MRI in the preoperative staging of mid‐low rectal cancer and its impact on clinical strategies

Abstract: Background: To determine the diagnostic accuracy of preoperative T/N stage with magnetic resonance imaging (MRI) in lower and middle rectal cancer patients and the impacts on clinical decision-making. Patients and methods: A total of 211 patients were recruited from October 2015 to March 2017 in this retrospective study. High-resolution MRI was performed within 2 weeks before surgery. Histopathologic results were evaluated for the postoperative T/N stage and the diagnostic accuracy of MRI was assessed accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…To further confirm the clinical feasibility of synthetic MRI, we evaluated T stage and EMVI using synthetic T2WI and conventional T2WI. The diagnostic accuracy of EMVI by two observers was consistent with previous studies [ 25 – 27 ], as was the T stage [ 28 30 ]. Although the diagnostic accuracy with conventional T2WI was slightly higher than that with synthetic T2WI, the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 89%
“…To further confirm the clinical feasibility of synthetic MRI, we evaluated T stage and EMVI using synthetic T2WI and conventional T2WI. The diagnostic accuracy of EMVI by two observers was consistent with previous studies [ 25 – 27 ], as was the T stage [ 28 30 ]. Although the diagnostic accuracy with conventional T2WI was slightly higher than that with synthetic T2WI, the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 89%
“…This improvement is meaningful for clinical decision-making, taking into consideration neoadjuvant therapy in patients with the latter, known as locally advanced rectal cancer. Overstaging may lead to overtreatment for patients with T1-2 tumors and an elevated risk for therapy-related morbidity and mortality, while the underestimation might lead to lower possibility of local control (35). In the present study, the computed diffusion images avoided 7 cases with T3 tumors from overstaging, and 5 cases with T3 tumors from underestimation, providing higher accuracy, sensitivity, and the specificity in detecting T3 tumors.…”
Section: Discussionmentioning
confidence: 60%
“…Regarding the accuracy of MRI, in the correct evaluation of the T descriptor of the TNM classification of rectal cancer, a very important role is played by the experience of the radiologist performing the investigation [42,43]. Thus, population studies have shown that the sensitivity of MRI in the correct evaluation of the T descriptor varies between 29 and 57% and the specificity varies between 50 and 83% [43][44][45][46][47]. These results are due, in part, to the experience of the examining physician and, on the other hand, to the difficulty of differentiating in some cases a stage T1 tumor from a stage T2 tumor.…”
Section: Local Staging In Rectal Cancer Using Mrimentioning
confidence: 99%